Investigation of impact resistance performance of pyramid lattice sandwich structure based on SPH-FEM. (1st April 2021) - Xue, Bing; Peng, Yu-Xiang; Ren, Shao-Fei; Liu, Nian-Nian; Zhang, Qi
Abstract: In this paper, we have studied the influence of the panel thickness on the underwater impact resistance performance of the pyramid lattice structure based on the SPH-FEM method. Firstly, a benchmark case is simulated and compared with the experimental results to verify the accuracy of SPH-FEM for fluid-structure interaction (FSI) problems. Then, the dynamic response of the pyramid lattice structure subjected to the shock wave is studied by the SPH-FEM coupling method. Also, the sandwich structure's deformation is compared with experimental results to verify the effectiveness of the presented method applied in the FSI problem. Based on this, we study several groups of pyramid lattice structures with different panel thicknesses. In terms of the deflection of the back panel and each part's energy-absorption rate, the influence of the thickness of the panel on the impact resistance of the pyramid lattice sandwich structure is studied in detail. The results of this paper can provide a reference for the design of the ship protection structure.